Integrated physiological, transcriptomic, and metabolomic analyses provide new insights into hypoxia tolerance in large yellow croaker (Larimichthys crocea) - Yibo Zhang; Jie Ding; Xuelei Wang; Ran Meng; Songpeng Jia; Xiongfei Wu; Junquan Zhu; XiaoMing Peng; Weiliang Shen (Marine Pollution Bulletin, 2026)

Microbial network fragmentation at a coal washing hotspot: Assembly mechanisms and stability implications - Senhua Jiang; Yangkun Shi; Jing Zhang; Chenyu Huang; Yue Li; Wenbo Zhang; Jinghui Ma; Nan Chen; Longfei Shu; Cheng Wang; Feifei Liu; Bo Wu (Applied Soil Ecology, 2026)

Microplastics type and size affected soil N2O emissions by governing contribution of nitrification and denitrification pathways - Xiaoqian Dan; Kaihui Du; Wangwang Tao; Jie Chen; Wenlan Yang; Chuangye Zhang; Junhao Li; Jing Hu; Qilin Zhu; Ahmed S. Elrys; Zucong Cai; Lei Meng; et al. (Applied Soil Ecology, 2026)

Diversity and drivers of marine heatwaves in the Beibu Gulf of the South China Sea - Bo Zhang; Qiang Wang; Lili Zeng; Kunshan Li; Yi Xie; Rui Shi (Climate Dynamics, 2026)

Dual RNA-seq Identifies Virulence Factors in Mesanophrys sp. and Immune Defenses in Portunus trituberculatus Hemocytes - Jianmei Hu; Yue Sun; Bo Zhang; Lujia Yang; Faisal Tasleem; Suming Zhou; Xiao Xie; Fei Yin (Acta Parasitologica, 2026)

Oomycete pathogens suppress litter decomposition in alpine meadow soils - Yu Nie; Bo Zhang; Yimin Zhao; Zhenhua Zhang; Shurong Zhou (Applied Soil Ecology, 2026)

Integrated plant-soil-microbiome responses mediate greenhouse gas emissions in the restoration of a semiarid steppe - Zhen Wang; Xiaojiang Yang; Paul C. Struik; Muhammad Nadeem Ashraf; Carmeron N. Carlyle; Scott X. Chang; Yuanheng Li; Wenbo Zhang; Riliga Wu; Baoming Ji; Ke Jin (Applied Soil Ecology, 2026)

Feature contributions and predictive modeling of aeolian sand transport detection in the atmospheric surface layer - Sai Li; Wenyong Ma; Junxiang Ma; Zhibo Zhang; Kang Yang (Aeolian Research, 2026)

Contrasting responses of surface and subsurface soil microbiome to ecological restoration in two types of steppe because of different changes in plant and soil properties - Xiaojiang Yang; Xiangjun Yun; Wenbo Zhang; Paul C. Struik; Shenyi Jiang; Xiangjian Tu; Ke Jin; Zhen Wang (Applied Soil Ecology, 2025)

Integrating soil biofilms: A holistic approach to understanding their role in soil health - Zhen Guo; Shuai Zhan; Peng Zhang; Peng Li; Bo Zhang (Applied Soil Ecology, 2025)

Elevation-dependent distribution of soil microbial necromass carbon in Pinus densata Mast. forests - Bo Zhang; Sijie Zhu; Liangna Guo; Ganggang Chen; Gengxin Zhang; Jiangrong Li (Applied Soil Ecology, 2025)

Long-term plastic film mulching promotes microplastic accumulation and alters gross nitrogen transformation in soil - Jinrui Zhang; Kai Wang; Tianxiang Hao; Jinbo Zhang; Christoph Müller; Perrine Florent; Hong Yan; Siyang Ren; Kaijing Qu; Kaige Ren; Jingjing Li; Yiting Su; et al. (Applied Soil Ecology, 2025)

Enhancing rice nitrogen use efficiency via plant-microbe-soil interactions: Insights from 15N tracing - Shending Chen; Chang Zhao; Wenyan Yang; Wenjie Wang; Qinying Zhu; Mengqiu He; Ahmed S. Elrys; Lei Meng; Han Meng; Zucong Cai; Jinbo Zhang; Christoph Müller (Applied Soil Ecology, 2025)

Metabolism, Function, Molecular Mechanism, and Application of Carotenoids in Coloration of Aquatic Animals - Yongguan Liao; Bo Zhang; Deshou Wang; Dongneng Jiang; Chunhua Zhu; Siping Deng; Huapu Chen; Guangli Li; Hongjuan Shi (Reviews in Aquaculture, 2025)
Among vertebrates, aquatic animals have a wide variety of body color. Yellow and red coloration, an important economic trait of aquatic animals, plays pivotal roles in ornamental value and consumption. Fish possess the most chromatophore types in vertebrates, and carotenoids primarily contribute to erythrophore and xanthophore pigmentation. Carotenoid metabolism and regulation of chromatophore development have long been a focus of selective breeding programs in fish. In crustaceans, carotenoids have been proven to be involved in enhancing coloration. However, the carotenoid requirements vary among different aquatic animals. The metabolic pathways in vivo and biochemical processes have not been well summarized. Thus, in this review, we introduced various types of carotenoids and their metabolic pathways in different aquatic species and described a similar mechanism of ketocarotenoid biosynthesis in fish and birds. We have focused on carotenoid metabolism processes and several significant genes involved in the coloration of vertebrates, such as scavenger receptors, apolipoproteins, ketolases, and β‐carotene oxygenase, and their applications in aquaculture. In addition, we also summarized the current problems of carotenoid addition in diets and emphasized the importance of aquatic breeding and molecular biotechnology in carotenoid coloration and ornamental fish breeding. Finally, we provided our perspectives on fish carotenoid pigmentation research and the aquatic industry. This review will enhance our understanding of fish carotenoid metabolism as well as provide deeper insights into the molecular mechanism of fish muscle and skin pigmentation. It will benefit the production of feed additives and selective breeding for ornamental aquatic animals.

Copper Homeostasis and Its Impact on Innate Immunity in Crustaceans - Hejia Chen; Xi Huang; Muhammad Tayyab; Mingming Zhao; Defu Yao; Zhihong Zheng; Xianliang Zhao; Yongzhen Zhao; Xiuli Chen; Bobo Zhang; Qiongqiong Yang; Yueling Zhang; et al. (Reviews in Aquaculture, 2025)
Copper, an essential micronutrient in crustaceans, plays vital roles in enzymatic processes, oxygen transport, pigmentation, and structural protein synthesis, including collagen and elastin. Recent research has elucidated its pivotal role in innate immunity of crustaceans, enhancing the immune response by promoting phagocytic activity, antimicrobial peptide production, and modulation of immune gene expression. Copper ions exhibit antimicrobial effects by disrupting cell membranes and inhibiting microbial proliferation. Furthermore, copper governs antioxidant defense mechanisms, protecting crustaceans against oxidative stress and infection. However, excessive copper can lead to toxicity, highlighting the need for strict maintenance of copper homeostasis. This review explores the complex processes of copper homeostasis in crustaceans, detailing transport mechanisms, storage proteins, and detoxification pathways. It emphasizes copper's critical physiological and immunological functions, contributing to a comprehensive understanding of its multifaceted roles in crustaceans and laying groundwork for further exploration of copper homeostasis as a strategy for boosting crustacean immunity. Aquaculture practices significantly influence copper levels in crustaceans. Effective copper management, including monitoring techniques, water treatment strategies, and regulatory frameworks, is crucial for both crustacean welfare and environmental sustainability.

Microbial mechanisms underlying active organic carbon pool increases via rhizodeposition by Moso bamboo under in situ crown 13CO2 enrichment - Man Shi; Hang Chen; Junbo Zhang; Zhenxiong Chen; Zhikang Wang; Tingting Cao; Quan Li; Xinzhang Song (Applied Soil Ecology, 2024)

Long-term effects of film mulching and fertilization regimes on gross N transformations in calcareous dryland soils - Na Gao; Ting Zhang; Zhaoyang Li; Xiaofan Tian; Jiayu Chen; Jinbo Zhang; Christoph Müller; Shiqing Li (Applied Soil Ecology, 2024)

Societal perceptions of aquaculture: Combining scoping review and media analysis - Mausam Budhathoki; Sezgin Tunca; Raquel Lopez Martinez; Wenbo Zhang; Saihong Li; Bertrand Le Gallic; Karen Brunsø; Priya Sharma; Piotr Eljasik; Gergo Gyalog; Remigiusz Panicz; David Little (Reviews in Aquaculture, 2024)
Aquaculture has been recognised for achieving multiple United Nations Sustainable Development Goals; its further growth depends on understanding, and responding to, societal perceptions in a broader context. Thus, this study aims to understand societal perceptions of aquaculture through a scoping review and media analysis. A scoping review identified 151 academic studies for inclusion in our five identified research clusters: (1) social acceptability, (2) growth and development, (3) media coverage, (4) sustainable aquaculture, and (5) consumer perceptions. Further, newspaper articles ( n = 100) were sampled from the United Kingdom, Denmark, France, Spain, Turkey, and China; elsewhere all articles identified were included (Poland, 79; Hungary, 29; India, 70). The findings suggest that scientific and newspaper articles tend to present sustainability aspects in a simplified form. Key stakeholder groups include fish farming enterprises, civil society, governmental officials, scientists, and business leaders both within aquaculture value chains (retailers/wholesalers, technology industry) and outside of them (fisheries, tourism). Also, other stakeholders included the public (indigenous groups, residents, consumers). The stakeholder groups perceived aquaculture differently and depending on the circumstances and context, their perceptions ranged from positive to negative. Many factors influenced their perceptions, including aquaculture's impact on multiple sustainability dimensions, knowledge, transparency, personal interests, types, and location of aquaculture practises, regulations, experience, and sociodemographic characteristics such as age, gender, education, and income. We recommend that aquaculture practitioners focus on context‐specific multifaceted strategies—prioritising transparency, communication, and accountability—and provide essential knowledge to ensure that societal perceptions of aquaculture are based on accurate, empirical information.

Understanding asymmetrical malpigmentation in flatfishes and improvement measures for aquaculture - Bo Zhang; Changwei Shao; Songlin Chen; Baolong Bao (Reviews in Aquaculture, 2022)
Pleuronectiformes, an order known as flatfishes, is important in mariculture worldwide with the unique characteristic of body asymmetry, and thus has value in scientific research. Also, as an economically important species, flatfishes have great developing potential for industrial aquaculture. Their rapid growth, rich nutrition, delicious taste, and high‐quality protein are accepted and favoured by consumers all over the world. Due to large‐scale breeding and expanding production, however, different degrees of abnormal body colour flatfishes have emerged, which seriously affect commercial value of the fish, even reducing it by half; therefore, relevant research has been carried out. This article reviews how environmental factors affect body colour abnormalities and possible genetic mechanism of abnormal body colouration of flatfishes, summarizes the hypotheses of the mechanism of body colour asymmetry, and proposes the latest improvement measures obtained at the genomic screening level to prevent the occurrence of abnormal body colour. This review suggests the molecular mechanism of abnormal asymmetric distribution of body colour, suggests measures for avoiding malpigmentation in flatfishes, and provides a constructive theoretical reference for healthy development of the flatfish breeding industry.

A comparative analysis of four internationally traded farmed seafood commodities in China: domestic and international markets as key drivers - Wenbo Zhang; Francis J. Murray; Liping Liu; David C. Little (Reviews in Aquaculture, 2017)
The historical development, current status and development trends of four internationally traded farmed seafood commodities, tilapia, penaeid shrimp, macrobrachium prawns and catfish in China were reviewed. China is the world's largest producer of tilapia, penaeid shrimp and macrobrachium prawns but, although farming of channel catfish and some indigenous catfish species is well developed, striped catfish failed to become established. In terms of global exports, China ranks first for tilapia and third for shrimp, while macrobrachium prawns and catfish mainly support domestic markets. Endogenous, biological characteristics and market demand explain the different courses of development and the differentiated focus on domestic and international trade. Tilapia and whiteleg shrimp production illustrated rapid growth in both domestic and international markets based on their favourable culture characteristics and well‐developed management systems. Huge production scale and domestic competition have resulted in China attaining a dominant and highly competitive position in the global tilapia market. High value of live freshwater prawns in local markets (and poor processing yield) has limited interest in exports, and local demand is also shifting the emphasis of shrimp production towards domestic markets, and a decline in its international market led to stagnation of channel catfish. Poor tolerance of seasonally low temperatures has restricted tilapia production to south China and completely inhibited the development of striped catfish as a commercial species. Live fish preference and costs of long‐distance transportation have restricted domestic consumption of tilapia. A balance between domestic consumption and export is required to optimise future growth opportunities for the industry.